How electric vehicles impact the power grid: A spatially high-resolution analysis of charging demand and power system dynamics - Jeon, Seungho; Roh, Minyoung; Kim, Muntae; Oh, Jaeick; Kim, Suduk (Energy Strategy Reviews, 2025)
Electrification is a primary strategy to achieve carbon neutrality. The expected surge in future electricity demand by battery electric vehicle (BEV) necessitates the reinforcement and construction of transmission and distribution (T&D) network. This study aims to evaluate the spatial heterogeneity impact of BEV adoption from the viewpoint of regionally balanced development on future T&D network under the ‘NetZero’ scenario. As a methodology, we developed and utilized the integrated assessment model, GCAM-EML, a version of global change analysis model (GCAM) with a regional resolution of 229 municipalities in South Korea. Under the ‘NetZero’ scenario, the national electricity demand is projected to increase by 2.18 times. Due to the rise in distributed power sources, the distribution of regional generation appears to be more uniform compared to the present or the ‘Ref’ scenario. On the other hand, electricity consumption of BEVs is predominantly focused in Seoul Capital Area, constituting 47 % of the national consumption. By computing the Gini coefficient based on the share of generation and BEV electricity consumption in each municipality, it was observed that under the ‘NetZero scenario’, the Gini coefficient decreases over time. This indicates an improvement in the ability of municipalities to meet BEVs' electricity demand locally, suggesting that the burden on T&D network due to future BEV adoption may decrease.
Keywords: Battery-electric vehicles; Change analysis; Electricity demands; Gini coefficients; High resolution; High-resolution integrated assessment model; Integrated assessment models; Netzero; Power grids; Transmission and distribution; Electric vehicle; Gini coefficient; High-resolution integrated assessment model; NetZero; Power grid